Nicotinic acetylcholine receptor-mediated effects of varenicline on LPS-elevated prostaglandin and cyclooxygenase levels in RAW 264.7 macrophages - Baris, Elif; Arici, Mualla Aylin; Tosun, Metiner (Frontiers in Molecular Biosciences, 2024)
Introduction: The purpose of this study is to delineate anti-inflammatory and antioxidant potential of varenicline, a cigarette smoking cessation aid, on decreasing lipopolysaccharide (LPS)-elevated proinflammatory cytokines in RAW 264.7 murine macrophage cultures which we showed earlier to occur via cholinergic anti-inflammatory pathway (CAP) activation. To this end, we investigated the possible suppressive capacity of varenicline on LPS-regulated cyclooxygenase (COX-1 and COX-2) via α7 nicotinic acetylcholine receptor (α7nAChR) activation using the same in vitro model. Materials and Methods: In order to test anti-inflammatory effectiveness of varenicline, the levels of COX isoforms and products (PGE2, 6-keto PGF1α, a stable analog of PGI2, and TXA2) altered after LPS administration were determined by Enzyme Linked Immunosorbent Assay (ELISA). The antioxidant effects of varenicline were assessed by measuring reductions in reactive oxygen species (ROS) using a fluorometric intracellular ROS assay kit. We further investigated the contribution of nAChR subtypes by using non-selective and/or selective α7nAChR antagonists. The results were compared with that of conventional anti-inflammatory medications, such as ibuprofen, celecoxib and dexamethasone. Results: Varenicline significantly reduced LPS-induced COX-1, COX-2 and prostaglandin levels and ROS to an extent similar to that observed with anti-inflammatory agents used. Discussion: Significant downregulation in LPS-induced COX isoforms and associated decreases in PGE2, 6-keto PGF1α, and TXA2 levels along with reduction in ROS may be partly mediated via varenicline-activated α7nAChRs.